Validitas Modul Kreatif Ekologi Berorientasi Guided Discovery untuk Mengembangkan Kreativitas Mahasiswa - Tilal Afian; Rizka Donny Agung Saputra (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
The purpose of this study was to describe the validity of the guided discovery-based ecological creative module to develop student creativity. This research is a qualitative descriptive study, to assess and obtain the quality of the creative ecology module. The instrument used in this study was a validation sheet. The module is validated by two experts in the field of biology education. The results showed that the guided discovery-based ecological creative module to develop student creativity was declared valid and reliable, so the module could be used in trials. Even though the module has been declared valid and reliable, it still needs to be tested for its practicality and effectiveness.